The Impact Of Workload And Work-Life Balance On Competitive Advantage Mediated By Digital Skills At Homedoki Company - Selvy Zahrah Ariqah Tambunan; Nisa Putri Fadhila; Retno Purwani Setyaningrum (Jurnal Manajemen Bisnis Eka Prasetya, 2025)
This study investigates the impact of workload and work-life balance on competitive advantage, with digital skills serving as a mediating variable. Utilizing a quantitative approach with causal design, data were collected and analyzed using Partial Least Squares (PLS) methodology. The findings reveal that both workload and work-life balance significantly influence competitive advantage. Moreover, digital skills partially mediate these relationships, with work-life balance showing a stronger mediation effect compared to workload. These results highlight the importance of managing workload, fostering work-life balance, and enhancing employees' digital skills as strategic measures to improve organizational competitiveness in a rapidly evolving business environment. This study provides insights for Homedoki Company to develop effective strategies aimed at enhancing employee well-being and sustaining market competitiveness.